(untitled) (Journal of Naval Architecture and Marine Engineering, 2011)
The corrosion resistance (weight loss) and mechanical properties (i.e. yield strength, ultimate strength and elongation) for three carbon steels, normal strength and high strength steels using tension test are investigated. The specimens are kept in chloride solution (20% NaCl) up to 240 hours. At every 48 hours, thickness and weight loss is measured and tension test is carried out. It was found that the susceptibility of the steels to corrosion based on their weight loss were identical prior to 144 hours, after that is accelerated for high strength steel. In addition, it was found that manganese (Mn) has reduced corrosion rate at early stage of corrosion. The change in mechanical properties by corrosion for all steels are the same, and ultimate strength is reduced, which for limit state design of aged structure should be taken into account. DOI: 10.3329/jname.v7i2.5309